1997
DOI: 10.2323/jgam.43.9
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of phenylalanine and production of other related compounds from phenylpyruvic acid and phenylacetic acid by ruminal bacteria, protozoa, and their mixture in vitro.

Abstract: Phenylalanine (Phe) synthesis and the production of other related compounds by mixed ruminal bacteria (B), protozoa (P), and a combination of the two mixture (BP) in an in vitro system were quantitatively investigated using phenylpyruvic acid (PPY) and phenylacetic acid (PAA) as substrates. Rumen microorganisms were collected from fistulated goats fed lucerne cubes (Medicago sativa) and a concentrated mixture twice a day. Microbial suspensions were anaerobically incubated at 39°C for 12 h. Phe and some other r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
19
1

Year Published

1998
1998
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 29 publications
6
19
1
Order By: Relevance
“…In the B suspension, large amounts of Trp were produced from IPA in the supernatants after 6-and 12-h incubations (Table 1). A small portion of Trp produced from IPA was incorporated into bacterial protein in 6-and 12-h incubations (Table 1), different from the results concerning Trp production from IND and serine (N. Mohammed et al, 1999) and Phe production from phenylpyruvate (PPY) and PAA reported by Amin and Onodera (1997). In total, 23.3 and 33.4% of IPA were converted to Trp after 6-and 12-h incubations, respectively.…”
Section: Production Of Trp From Ipacontrasting
confidence: 50%
See 1 more Smart Citation
“…In the B suspension, large amounts of Trp were produced from IPA in the supernatants after 6-and 12-h incubations (Table 1). A small portion of Trp produced from IPA was incorporated into bacterial protein in 6-and 12-h incubations (Table 1), different from the results concerning Trp production from IND and serine (N. Mohammed et al, 1999) and Phe production from phenylpyruvate (PPY) and PAA reported by Amin and Onodera (1997). In total, 23.3 and 33.4% of IPA were converted to Trp after 6-and 12-h incubations, respectively.…”
Section: Production Of Trp From Ipacontrasting
confidence: 50%
“…The continuous engulfment of bacteria by protozoa can lower the number of bacteria and decrease the total bacterial activity to synthesize Trp from IPA. In this connection, Amin and Onodera (1997) also reported the same effect during the production of Phe from PPY and PAA by B, P, and BP suspensions.…”
Section: Production Of Trp From Ipamentioning
confidence: 54%
“…The large amounts of PAA produced from PPY and the production of PAA in the B, P and BP suspensions with and without SL and B 6 are shown in Table 1. PAA production from PPY was almost similar to a result reported previously (Amin and Onodera, 1997b).…”
Section: Effects Of Salinomycin and Vitamin B 6 On The Metabolism Of supporting
confidence: 80%
“…PAA was converted mainly to Phe, and the production of Phe in B, P and BP suspensions with and without SL and B 6 is shown in Table 2. The production of Phe from PAA was almost similar to results reported previously (Amin and Onodera, 1997b). In B suspensions without additives, 174 and 240 µmol/g MN (168 and 231 µM) of PAA were converted to Phe, while the production of Phe with SL tended to be inhibited, though not significantly, by 12.1 and 3.8% during the 6 and 12 h incubation periods.…”
Section: Effects Of Salinomycin and Vitamin B 6 On The Metabolism Of supporting
confidence: 75%
See 1 more Smart Citation